Extracellular Mitochondria Signals in CNS Disorders - Park, Ji-Hyun; Hayakawa, Kazuhide (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria actively participate in the regulation of cell respiratory mechanisms, metabolic processes, and energy homeostasis in the central nervous system (CNS). Because of the requirement of high energy, neuronal functionality and viability are largely dependent on mitochondrial functionality. In the context of CNS disorders, disruptions of metabolic homeostasis caused by mitochondrial dysfunction lead to neuronal cell death and neuroinflammation. Therefore, restoring mitochondrial function becomes a primary therapeutic target. Recently, accumulating evidence suggests that active mitochondria are secreted into the extracellular fluid and potentially act as non-cell-autonomous signals in CNS pathophysiology. In this mini-review, we overview findings that implicate the presence of cell-free extracellular mitochondria and the critical role of intercellular mitochondrial transfer in various rodent models of CNS disorders. We also discuss isolated mitochondrial allograft as a novel therapeutic intervention for CNS disorders.